The value of names: civil society, information, and governing multinationals on the global periphery - Kreitmeir, D; Lane, N; Raschky, PA (University of Oxford, 2022)
Civil society plays a crucial role in governance where laws and authority are weak. Increas-ingly, multinationals operate in these complex environments. We study how a key strategy of international civil society—disseminating information about human rights abuse—impacts multi-nationals. To do so, we focus on trends at the center of international campaigns: the assassination of activists, and collect 20 years of data related to murders associated with the global mining sector. Using event study methodology, we estimate the impact of human rights reporting on the stock price of firms connected to events. We find that the effect of the human rights spotlight is substantial. Firms named in assassination coverage have large, negative abnormal returns following assassinations. Our estimates imply a median loss in market capitalization of 100 million USD. Meanwhile, these events do not impact the social responsibility scores of firms. We show that the media plays a crucial role in these effects: the negative impact of assassinations is strongest when they coincide with calm news cycles versus peak news cycles, when news may be crowded out by large, international stories. In addition, we argue our results are driven by events where companies are explicitly named in the reporting. Last, we show that assassinations are positively related to the royalties paid by mining projects to domestic governments. JEL: O16, O17, D74, G3, G14, L82